The Workplace Spirituality With Employee Performance And Productivity : A Case Study Of Education Sector At Selected School In Betong, Sarawak - Cathrinna, Peter (Universiti Malaysia Sarawak (UNIMAS), 2020)
Workplace spirituality is a framework of an organization values demonstrated in culture that promote the transcendent employee experience through the working process and facilitate their sense of connected to others so that they feel complete and joyful. However, this aspect is not fully realize because it is not fully understood, religious preferences, and organizational cultures. This study is aim to study the workplace spirituality with employee performance and productivity in a selected educational sector in Betong, Sarawak informants interviewed who were currently work in the selected school at Betong, Sarawak. The interview session was using in-depth interview. The population of this study was targeting the secondary teachers by using a purposive sampling. The data from the interview were manually analysed using content analysis. The research instrument had been using the interview guide questions based on the research questions of this study. Based on the research findings, all informants believed that workplace spirituality success and efficiency. All informants agree that spirituality in the workplace is important in shaping performance and productivity for employees. This research will also show that there are also various definitions based on their respective beliefs in this spirituality. In this study can also prove some spiritual importance in the workplace and identify its impact on the performance and productivity of employees. Furthermore, this study was able to identify some spiritual issues in the workplace. Around the same time, this report has suggested recommendations to enhance employee’s efficiency and profitability by doing spiritual practice. At the end of this paper, there are several recommendations to the organization, human resource practitioners and future researcher in conducting the research in the future